PENGKAJIAN BESARAN BIAYA KECELAKAAN LALU LINTAS ATAS DASAR PERHITUNGAN BIAYA KORBAN KECELAKAAN STUDI KASUS BANDUNG, CIREBON DAN PURWOKERTO - Agus Bari Sailendra (Jurnal Jalan-Jembatan, 2008)
Almost every year the number of dead victims caused by traffic accidents in Indonesia reached 10.000 persons, excluding the loss of seriously and slight injured victims and the loss of materials. The effect of the accidents increased the cost of road users, and economically made inefficient use of resources. Efforts to handle the accidents, before (prevention) and after (reduction) the occurence of the accidents, have been continuously performed. However, the results are not maximum yet since the economic approach is not taken into account. One of the economic considerations needed is to find out the benefit of the investment in handling the accidents. For this reason, a study of accident costs, specifically based on the costs paid by the accident victims was conducted by the Transport Research Laboratory (TRL, UK) in collaboration with the Center of Research and Development of Road and Bridge in 1993. The study conducted using the Gross Output or Human Capital Approach in three towns found that the accident costs for dead, seriously injury, and slightly injury victims were Rp. 119,015,893,- , Rp. 4,973,889,- , and Rp. 946,506,- respectively. In addition, the costs related to the vehicle damage and the costs for handling the accidents were not included in this study. Kewords: Traffic Accidents, Accident Victims, Gross Output, and Human Capital Approach